Bink and gollie - DiCamillo, Kate.; McGhee, Alison, 1960-; Fucile, Tony (2016)
Two roller-skating best friends--one tiny, one tall--share three comical adventures involving outrageously bright socks, an impromptu trek to the Andes, and a most unlikely marvelous companion.
K-3.
510L
2.5
Electronic reproduction.
M
SORA electronic book.
Keywords: SORA electronic book; Friendship -- Juvenile fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Adventure fiction; Humorous fiction